Drosophila 4EHP is essential for the larval-pupal transition and required in the prothoracic gland for ecdysone biosynthesis. - Valzania, L.; Ono, H.; Ignesti, M.; Cavaliere, V.; Bernardi, F.; Gamberi, C.; Lasko, P.; Gargiulo, G. (Developmental Biology, 2016)
Maternal expression of the translational regulator 4EHP (eIF4E-Homologous Protein) has an established role in generating protein gradients essential for specifying the Drosophila embryonic pattern. We generated a null mutation of 4EHP, which revealed for the first time that it is essential for viability and for completion of development. In fact, 4EHP null larvae, and larvae ubiquitously expressing RNAi targeting 4EHP, are developmentally delayed, fail to grow and eventually die. In addition, we found that expressing RNAi that targets 4EHP specifically in the prothoracic gland disrupted ecdysone biosynthesis, causing a block of the transition from the larval to pupal stages. This phenotype can be rescued by dietary administration of ecdysone. Consistent with this, 4EHP is highly expressed in the prothoracic gland and it is required for wild type expression levels of steroidogenic enzymes. Taken together, these results uncover a novel essential function for 4EHP in regulating ecdysone biosynthesis.